ANALISIS ANTESEDEN PERILAKU NIAT MEMBELI PELANGGAN PADA KFC SOLO SQUARE - Utomo, Cahyo (Riset Manajemen & Akuntansi, 2014)
The purpose of this study was to examine the role of the influence of the quality of the physical environment, quality of food, quality of service, restaurant image, perceived value and customer satisfaction on behavioral intentions of buying customers. Specifically, this study wanted to test whether the quality of the physical environment, quality of food, quality of service, restaurant image, perceived value and customer satisfaction mempuyai important role in shaping customer buying intentions at KFC Solo Square. Survey methods used to collect the data. In this study, the sample consisted of 200 people who want to repurhase into KFC Solo Square. Purposively selected engineering methods make it easier to get a sample. Reliability and validity tests were conducted to test the quality of the data. The statistical method is selected for each SEM (structural equation model) is used to describe the relationship between the observed variables. The results showed that quality physical environment no significant effect on restaurant image, quality physical environment, food quality, and service quality no significant effect on perceived value, restaurant image a significant effect on the perceived value, perceived value significant effect on consumers satisfaction, and consumers satisfaction significantly behavioral intentions towards customers.